Are people with children happier than childless in Lithuania? Sources and methods of assessment - Galdauskaitė, Dovilė (Lithuanian Journal of Statistics, 2018)
[full article and abstract in Lithuanian; abstract in English]Fertility decline and unstable fertility rates are currently observed in developed countries, including Lithuania. To account for these undergoing instabilities new theories and methods of formal demography have been proposed. The aim of this research is to analyse links between fertility and happiness in Lithuania. This study is based on a newly developed theory that links happiness and childbearing. The study refers to data analysis of three international level surveys – Fertility and Family (1994-1995), Population and Policy Acceptance (2001) and Generations and Gender (2006). The main method of analysis – binary logistic regression. Results of data analysis support the hypothesis, that there is a relationship between happiness and fertility, although ambiguous.
Keywords: fertility; childbearing; happiness; logistic regression